Learning Human Reproductive System with Contextual Teaching Learning (CTL) Approach for Grade 6 Students at State Elementary School 011 Sangatta Selatan - Resti Novia Rahayu; Farida Catur Wahyu Anggriyani (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This study aims to examine in depth the effectiveness of the Contextual Teaching and Learning (CTL) approach in learning the human reproductive system for grade 6 students at SDN 011 Sangatta Selatan. The CTL approach was chosen because it can relate learning material to the context of students' daily lives, so it is expected to increase students' understanding and involvement in learning. The research method used was qualitative research with a case study approach. Data were collected through observation, in-depth interviews, and document analysis. The results showed that the implementation of the CTL approach not only improved students' understanding, but also motivated them to be more active in the learning process. The findings suggest that the CTL approach is effective in improving the quality of biology learning in elementary schools